2016
DOI: 10.1093/nar/gkw1154
|View full text |Cite
|
Sign up to set email alerts
|

Functional RNAs: combined assembly and packaging in VLPs

Abstract: We describe here a one pot RNA production, packaging and delivery system based on bacteriophage Qβ. We demonstrate a method for production of a novel RNAi scaffold, packaged within Qβ virus-like particles (VLPs). The RNAi scaffold is a general utility chimera that contains a functional RNA duplex with paired silencing and carrier sequences stabilized by a miR-30 stem-loop. The Qβ hairpin on the 5΄ end confers affinity for the Qβ coat protein (CP). Silencing sequences can include mature miRNAs and siRNAs, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 47 publications
0
42
0
Order By: Relevance
“…The recent termination of Phase I clinical study on synthetic miR-34a mimic (MRX34) (Beg et al, 2017), owing to high incidence of adverse immune responses, again testifies the body's capability to distinguish chemoengineered RNAi agents as foreign. Therefore, biologic approaches such as in vitro transcription (Beckert and Masquida, 2011) and, especially, bioengineering in live cells (Ponchon and Dardel, 2007;Ponchon et al, 2009;Huang et al, 2013;Li et al, 2014Li et al, , 2015Li et al, , 2018Chen et al, 2015;Wang et al, 2015;Pereira et al, 2016;Fang et al, 2017), are highly warranted to produce natural RNA molecules that should better represent cellular ncRNA properties for basic research and experimental therapy (Ho and Yu, 2016;Pereira et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The recent termination of Phase I clinical study on synthetic miR-34a mimic (MRX34) (Beg et al, 2017), owing to high incidence of adverse immune responses, again testifies the body's capability to distinguish chemoengineered RNAi agents as foreign. Therefore, biologic approaches such as in vitro transcription (Beckert and Masquida, 2011) and, especially, bioengineering in live cells (Ponchon and Dardel, 2007;Ponchon et al, 2009;Huang et al, 2013;Li et al, 2014Li et al, , 2015Li et al, , 2018Chen et al, 2015;Wang et al, 2015;Pereira et al, 2016;Fang et al, 2017), are highly warranted to produce natural RNA molecules that should better represent cellular ncRNA properties for basic research and experimental therapy (Ho and Yu, 2016;Pereira et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…13,14 The packaging of RNA by protein(s) in vivo, in coupled RNA production and packaging systems, may be effective for overcoming at least a subset of these challenges. 15 RNA expression in vivo [16][17][18] can employ recombinant nucleic acids that encode polymerase promoters, affinity tags, functional 'target' sequences and genes for packaging proteins.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Qb VLPs are hollow with pores 1.4 nm in diameter. 20 Lau et al 22 and Fang et al 15 previously demonstrated packaging of non-viral RNA in Qb VLPs by co-expressing target RNA and CP from distinct plasmids in E. coli. In vivo packaging of target RNA in VLPs is promoted by an RNA hairpin (hp), derived from Qb RNA, which has high affinity for CP ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…As is well known, virus RNA carrier exhibits high transfection efficiency, but at the cost of strong immunogenicity. Virus‐like nanoparticles have therefore been developed as gene and drug carriers from different plant protein or Hepatitis B core protein …”
Section: Nanomaterials For Cancer Precision Therapymentioning
confidence: 99%